An Android-Based Aerobic Exercise Application to Easily Decrease Symptoms of Ischemic Stroke - Eviyanti Khasanah; Rakhmat Susilo (UM Purwokerto Press, 2022)
Background: Recurrent stroke occurs due to the lack of knowledge about symptom improvement in ischemic stroke, so many people ignore it. A researcher said aerobic exercise improves cardiovascular health, balance mobility, and endurance after a stroke. This has health consequences that can affect the occurrence of subsequent recurrent strokes. Aerobic exercise is an application designed as a medium for health education. Objective: This technological work aims to determine the application of Low Impact Aerobic Exercise to improve ischemic stroke symptoms. Method: At this stage, a trial was conducted on the features of the Aerobic Exercise application using an expert test, namely a trial conducted by consulting research instruments (applications) with experts or health experts. After that research was carried out. Results: Changes in improving ischemic stroke symptoms after using aerobic exercise applications on blood pressure, cholesterol, and muscle mobilization were found. Conclusion: The Aerobic Exercise application for respondents is easy to use, and they understand how to operate it.